Geoelectrical investigation to delineate the groundwater potential aquifers in Chittar river basin, Southern India. Issue 4 (2nd October 2021) - Nair, Nithya C.; Srinivas, Y.; Rajkumar, S.; Arun Bose, S.
ABSTRACT: Study on electrical resistivity of the subsurface helps to evaluate the geoelectrical parameters and groundwater potential of river basin. Chittar river basin falls under the hard rock terrains of Tamil Nadu, so, weathered and fractured horizons may be the target of groundwater. Sixty vertical electrical soundings were conducted to understand the groundwater potentiality in Chittar basin. The inverted results of the sounding data reveal that the study area is characterized by four to five geoelectric layers. From the interpreted results, it was observed that aquifers in 32 VES locations are found to have moderate to good productivity. This study reveals that top layer is mostly thin soil cover followed by weathered or semi-weathered rock. The aquifer in most of the study area is found in the second layer and majority of these VES stations are located along the river course, so the aquifer is shallow in nature. D-Z parameters like longitudinal conductance and coefficient of anisotropy also support the interpretation.